[Erratum] Oxidative Stress Mediates the Association between Thyroid Dysfunction and Breast Cancer - Maira Mahmood; Mazhar Mushtaq; Aamenah Malik; Rukhshan Khurshid; Faiza Aamir; Arham Javed (Indonesian Biomedical Journal)
The publisher would like to point out that the heading of Table 2, Table 3 and Figure 1 were incorrectly printed. The following headings are correct.